Hybridization potential and genetic influence of parental varieties on fruit size and set rate in Gleditsia sinensis - Qingying Zeng; Yang Zhao; Xiurong Wang; Fuhua Liu; Meixuan Xie; Xingfu Zhang (Scientific Reports)
Abstract Gleditsia sinensis is a dioecious perennial tree, with its fruit size directly impacting its economic value. Investigating the feasibility of hybridization between different Gleditsia varieties and the influence of parentage on fruit size is crucial. In this study, we compared the pollen viability of Gleditsia sinensis, Gleditsia japonica var. delavayi (G. delavayi), Gleditsia japonica and Gleditsia fera under long-term storage, and explored the feasibility of intraspecific and interspecific hybridization of Gleditsia sinensis. We also evaluated the genetic characteristics of parentage on the fruit size and fruit set rate of Gleditsia sinensis. The results indicated that dry storage at -80 °C is suitable for the long-term preservation of pollen for most Gleditsia varieties. Interspecific hybridization of G. sinensis is feasible, and hybridization with G. fera exhibits a high general combining ability for fruit size. Therefore, G. fera can serve as an excellent male parent for interspecific hybridization with G. sinensis. The phenotypic traits of the current generation’s pods are primarily influenced by the additive effects of the maternal parent and the non-additive effects of both parents. Pod length and width exhibit high heritability, while pod thickness has lower heritability and is more significantly influenced by non-additive effects.